UMP receives visit from Petrosains - Nurul Hazlina, Noordin (2023)
PEKAN, 16 June 2023 – A delegation from Petrosains, led by its CEO En Ezarisma Azni Mohamad, recently visited the UMP STEM Lab, accompanied by esteemed members of the Petrosains team.